The CALHM1 P86L polymorphism is a genetic modifier of age at onset in Alzheimer’s disease: a meta-analysis study - Lambert, Jean-Charles (2010)
The only established genetic determinant of non-Mendelian forms of Alzheimer’s disease (AD) is the ε4 allele of the apolipoprotein E gene (APOE). Recently, it has been reported that the P86L polymorphism of the calcium homeostasis modulator 1 gene (CALHM1) is associated with the risk of developing AD. In order to independently assess this association, we performed a meta-analysis of 7,873 AD cases and 13,274 controls of Caucasian origin (from a total of 24 centres in Belgium, Finland, France, Italy, Spain, Sweden, the UK and the USA). Our results indicate that the CALHM1 P86L polymorphism is likely not a genetic determinant of AD but may modulate age at onset by interacting with the effect of the ε4 allele of the APOE gene.